Living and dead foraminiferal assemblages from an active submarine canyon and surrounding sectors: the Gioia Canyon system (Tyrrhenian Sea, Southern Italy). (May 2017) - Letizia, Di Bella; Martina, Pierdomenico; Roberta, Porretta; Chiocci, Francesco Latino; Eleonora, Martorelli
Abstract: Living (rose Bengal stained) and dead benthic foraminiferal assemblages were studied from 23 stations located between 60 and 670 m depth along the Gioia Canyon and the adjacent continental shelf and slope (Southern Tyrrhenian Sea). The aim of this study is to investigate the relationships among sedimentary processes, hydrological patterns and benthic foraminiferal distribution, in a highly dynamic environment. High sedimentation rates on the shelf and occasional turbidity flows along the canyon, lead to unstable environmental conditions at the seafloor that reflect on the microbenthic community influencing faunal density, diversity, species composition and distribution inside the sediment. The foraminiferal distribution seems to be controlled by sedimentary processes, nutrient supply and organic matter recycling, which in turn are strongly controlled by the seasonal variability of riverine inputs and current dynamics in the Gulf of Gioia. From the inner shelf to the upper continental slope (550 m depth), the living foraminiferal assemblage is dominated by agglutinated taxa, likely favored by the high terrigenous supply. Frequent eutrophic taxa ( Valvulineria bradyana and Nonionella turgida ) tolerant high turbidity ( Leptohalysis scottii, ) and low oxygen ( Bolivina spp. and Bulimina spp.) are recorded on the edge of the inner shelf, where channeling, deposition of coastal deposits and occasional sediment gravity flows occur. In the outer sector of the shelf a turnover of species is observed; L . scottii replaced by the opportunistic species Reophax scorpiurus, and taxa indicative of high energy conditions ( Cassidulina spp.) become dominant in association with mesotrophic species like Globocassidulina subglobosa . Along the continental slope, lower sedimentation rates and more stable environmental conditions support richer and more diversified foraminiferal assemblage. The abundance of Bulimina marginata indicates eutrophic conditions at the shallower station (300 m depth) whereas at greater depth (550 m) typical open slope species dominate ( Gyroidina spp., Uvigerina mediterranea ). Within the Gioia Canyon, benthic assemblage indicates environmental conditions similar to those observed in other Mediterranean and extra-Mediterranean canyons. The assemblage is characterized by eutrophic and low oxygen taxa ( Bolivina spp., Bulimina spp.) in relation to periodical fluxes of sediment and organic matter. Similar relationships arise from the analysis of dead foraminiferal assemblages. However, the comparison between living and dead faunas highlight compositional and structural changes related to taphonomic processes. Highlights: Environmental characterization of canyon system in the Tyrrhenian margin is proposed. New sedimentological and microfaunal data are provided. Sedimentary processes and riverine inputs effects on microbenthic assemblages.